2016
DOI: 10.1186/s40064-016-3142-0
|View full text |Cite
|
Sign up to set email alerts
|

Water temperature induces jaw deformity and bone morphogenetic proteins (BMPs) gene expression in golden pompano Trachinotus ovatus larvae

Abstract: Golden pompano Trachinotus ovatus larvae were kept at 26, 29 and 33 °C for 15 days from 3-day post hatching (DPH) to 18 DPH to test temperature-dependent growth and jaw malformation. The growth, survival, jaw deformity and the gene expressions of bone morphogenetic proteins (BMPs) were used as criteria to examine the fish response to temperature manipulation. The growth rate of fish at 29 or 33 °C was significantly faster than fish at 26 °C, while fish survival at 29 °C was significantly higher than fish at 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…The optimal temperatures for the maximum sperm motility of key farmed fish of the tropical regions such as tiger grouper, barramundi, red snapper, pompano, and cobia are 28-30℃, which is similar to the optimal range for their growth (Glencross & Felsing, 2006;Le et al, 2011Le et al, , 2014Le et al, , 2020Ma et al, 2016). In the current study, we found that MOT, VAP, and DSM were highest at 30℃ which is consistent across three periods during the spawning season.…”
Section: Fertility Trialssupporting
confidence: 80%
“…The optimal temperatures for the maximum sperm motility of key farmed fish of the tropical regions such as tiger grouper, barramundi, red snapper, pompano, and cobia are 28-30℃, which is similar to the optimal range for their growth (Glencross & Felsing, 2006;Le et al, 2011Le et al, , 2014Le et al, , 2020Ma et al, 2016). In the current study, we found that MOT, VAP, and DSM were highest at 30℃ which is consistent across three periods during the spawning season.…”
Section: Fertility Trialssupporting
confidence: 80%
“…A positive relationship between bmp4 expression and ossification has been established in different groups of vertebrates including fish ( Chen et al, 2002 ; Albertson et al, 2005 ). bmp4 is expressed in osteoblasts prior to formation of mineralized bone nodules being indicative of new bone formation, although high levels of expression have been also reported in response to elevated temperatures, and linked to increased jaw malformations ( Ytteborg et al, 2010 ; Ma et al, 2016 ). Indeed, bmp4 has been shown to play a role in jaw development ( Albertson et al, 2005 ) and more recently, in the determination of intermuscular bone distribution ( Su and Dong, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On 10 day, the expression of BMP2, BMP4, and BMP5 genes were all upregulated, also indicating that HT induced the development of vertebral cartilage. The studies of Ma et al (2016a) also show that the increase of water temperature increased the expression of BMPs and resulted in an increase in the rate of jaw deformity in T. ovatus larvae. At the later stage of the experiment (30 days), the expressions of BMPs were relatively down-regulated in the HT group, which may be related to the adaptability of fish to water temperature.…”
Section: Effects Of High Water Temperature On Genes Related To Chondrocyte Developmentmentioning
confidence: 88%
“…Abnormality of bone results in a bottleneck in the culture of T. ovatus. The effects of temperature and nutrition factors on the skeletal deformities of T. ovatus, and the expression of some genes related to skeletal development in T. ovatus has also been studied (Ma et al, 2016a(Ma et al, , 2017a(Ma et al, ,b,c, 2018Yang et al, 2016), but the regulatory mechanism of temperature on the occurrence of vertebral fusion in juvenile T. ovatus is still not clear, while histopathological studies on the skeleton of T. ovatus are lacking. The objective of the present study was to elucidate the possible molecular reaction of vertebral fusion in juvenile T. ovatus under high water temperature combined with the histopathology.…”
Section: Introductionmentioning
confidence: 99%